An enduring lesson from Thailand's economic performance - Amin, A. T. M. Nurul (1996)
Although the technical details in maintaining macroeconomic stability, rapid expansion of manufacturing exports, attracting foreign investment, promoting market dynamism, and private-public sector cooperation bear mNy insights for possible emulation by other developing countries seeking economic growth, the paper argues that the most enduring lesson from Thailand's economic success lies in the arena of political economy that allowed a typical, tropical underdeveloped country with high population growth, huge underemployment, subsistence agricultural economy, widespread illiteracy, pervasive corruption, perennial political instability, repeated coups and counter coups, authoritarian and dictatorial rule, intermittent and transitory period of failed democratic polity and even armed insurgency-finally to leave all this behind. The political economy lessons are that a technocratic management of an economy for maintaining a continuity of economic policy through swings of political pendulum of democratic striving a and military-autocratic reigns and an early emergence and embracing of a business-enterprise culture, as opposed to a culture of destructive political protests and dissents, are essential for economic growth.
Keywords: Thailand -- Literary collections